What Accounts for the Union Member Advantage in Voter Turnout? Evidence from the European Union, 2002-2008 - Bryson, Alex; Gomez, Rafael; Kretschmer, Tobias; Willman, Paul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2014)
Across countries, union membership and voter turnout are highly correlated. In unadjusted terms, union members maintain a roughly 0.10 to 0.12 point gap in voting propensity over non-members. We motivate empirically and propose a model—with three causal channels—that explains this correlation and then empirically tests for the contribution of each channel to the overall union voting gap. The first channel by which union members are more likely to vote is through the so-called "monopoly-face" of unionism (i.e., unionization increases wages for members and higher incomes are a significant positive determinant of voting). The second is the so-called "social custom" model of unionism, which argues that union co-worker peer pressure creates incentives to vote amongst members for the purpose of having cast a ballot or being seen at the voting poll. The third and final channel is based on the "voice-face" of unionism whereby employees who are (or have been) exposed to the formalities of collective bargaining and union representation at the workplace are also more likely to increase their attachment to structures of democratic governance in society as well. We test to see how much of the raw "union voting premium" is accounted for by these three competing channels, using contemporary data from 29 European countries. We find that all three channels are at work, with voice the dominant effect (half of the overall gap attributed to this channel) and the other two (monopoly and social custom), each accounting for approximately one-fourth of the overall union voting gap.